The Farce of Law: Performing and Policing Norm and Ahmed in 1969 - Karen Crawley (Law Text Culture, 2010)
Late one night on a deserted street, Norm, a working class Anglo-Australian male, stops Ahmed, a younger student from Pakistan, to ask him for a light, and strikes up a conversation. Norm seems friendly enough, but there is an undercurrent of hostility to his speech and behaviour, as if he is slyly baiting or taunting Ahmed. When the conversation draws to a close, Norm offers a parting handshake to Ahmed which suddenly becomes a punch to the stomach and face. ‘He grabs Ahmed’s head and bashes it against the post. Then he flings the limp body over the handrail’ (Buzo 1968: 26). Norm then utters the final, shocking words: ‘Fuckin’ boong’.